Perceptions of HPV and attitudes towards HPV vaccination among men who have sex with men: a qualitative analysis. (November 2016) - Nadarzynski, Tom; Smith, Helen; Richardson, Daniel; Pollard, Alex; Berglund, Anja; Hurst, Sarah; Llewellyn, Carrie
Abstract: Background: Men who have sex with men (MSM) are at risk of genital warts and anal cancer due to human papillomavirus (HPV) infection. From 2016, MSM are being targeted for HPV vaccination in the UK through sexual health settings. This study explored perceptions of HPV and HPV vaccination among MSM. Methods: Focus groups and one-to-one interviews with self-identified MSM from Brighton, UK, were conducted between Nov 20, 2014, and March 15, 2015. Participants were recruited from community-based lesbian–gay–bisexual–transgender venues and organisations. Discussions were recorded, transcribed verbatim, and analysed with framework analysis. Ethics approval was granted from Brighton and Sussex Medical School. Findings: 33 men took part (median age 25 years, IQR 21–27), most of whom did not know about HPV (n=25), anal cancer (31), or HPV vaccination (26). Whereas genital warts and anal cancer were perceived as severe, men did not perceive themselves at risk for HPV. All MSM would accept the HPV vaccine if offered by a health-care professional. The inability to self-identify as gay or bisexual, access to sexual health services, and discussing sexuality with health-care professionals were barriers to HPV vaccination. Two MSM were concerned that selective HPV vaccination would increase stigma and prejudice comparable to the AIDS epidemic. Ten MSM were unsure about the effectiveness of HPV vaccination for sexually active men and were in favour of vaccinating all adolescent boys at school. Interpretation: Most MSM have poor knowledge about HPV and associated anal cancer. Despite the lack of concern about HPV-related diseases, MSM would be willing to receive the HPV vaccine. There is a need for health education about the risk of HPV and HPV-related diseases so that MSM can appraise the benefits of the HPV vaccine for their health. Concerns about HPV vaccine effectiveness in sexually active men and possible stigmatisation need to be addressed to increase HPV vaccine acceptability. Funding: This work was funded through a competitive PhD scholarship from the University of Brighton.